Peningkatan Keterampilan Kewirausahaan Bagi Ibu-Ibu PKK Melalui Pelatihan Bisnis Rumahan di Desa Jipang, Karanglewas - Puspita Lianti Putri; Budi Widadi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Jipang Village, located in Karanglewas Subdistrict, is an area rich in natural resources and has great potential for the development of home businesses. However, most of its residents, especially the women who are members of the PKK group (Family Welfare Development), have not been able to maximize this potential to improve their economic well-being. Several key factors hindering this include a lack of knowledge and skills in entrepreneurship, limited access to technology and information, and insufficient opportunities to receive adequate business training. Through this entrepreneurship training program, it is hoped that the PKK women will be empowered to develop their home businesses more professionally and effectively, thereby increasing family income and reducing poverty levels in Jipang Village.